2023
DOI: 10.1007/s12028-022-01672-3
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Dysfunction After Traumatic Brain Injury: An Ignored Clinical Syndrome?

Abstract: Traumatic brain injury (TBI) incurs substantial health and economic burden, as it is the leading reason for death and disability globally. Endocrine abnormalities are no longer considered a rare complication of TBI. The reported prevalence is variable across studies, depending on the time frame of injury, time and type of testing, and variability in hormonal values considered normal across different studies. The present review reports evidence on the endocrine dysfunction that can occur after TBI. Several aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…In the context of brain injury, at least partial hypopituitarism (gonadal axis) is frequently documented, but persistent hypopituitarism occurs only in max. 11% of these patients [ 64 , 65 ]. Similarly, radiation therapy to head and neck structures or the pituitary gland can lead to hypopituitarism over time and should be suspected in the presence of a corresponding clinical picture [ 66 , 67 ].…”
Section: Unknown Hypopituitarism and Hospitalization For A Medical Or...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of brain injury, at least partial hypopituitarism (gonadal axis) is frequently documented, but persistent hypopituitarism occurs only in max. 11% of these patients [ 64 , 65 ]. Similarly, radiation therapy to head and neck structures or the pituitary gland can lead to hypopituitarism over time and should be suspected in the presence of a corresponding clinical picture [ 66 , 67 ].…”
Section: Unknown Hypopituitarism and Hospitalization For A Medical Or...mentioning
confidence: 99%
“…Pituitary disorders are often overlooked in patients with TBI and aSAH because they present with non-specific symptoms, potentially leading to delayed recognition and a worse prognosis [ 87 ]. Specifically, clinical manifestations range from generalized fatigue and headache to more specific signs such as amenorrhea or lack of libido, with the most common deficiencies reported being growth hormone, ACTH, and gonadotropins, although the prevalence may vary with time since injury [ 65 , 88 , 89 ]. Thereby, the acute phase after TBI or aSAH is characterized by clinically significant abnormalities such as ACTH-cortisol deficiency and salt-water imbalance, which can be life-threatening and associated with increased morbidity and mortality [ 90 ].…”
Section: Management Of Hospitalized Patients With Hypopituitarism Fol...mentioning
confidence: 99%
“…Thus, the fact that female sex is reported as a risk factor for developing persistent PCS symptoms could be associated with sexual endocrine monthly regulation or muscular particularities and may not contribute to the similarity between persistent PCS and FNDs. However, several recent studies found that mTBI could lead to pituitary dysfunctions [51][52][53][54] that could further increase the risk for developing persistent headaches [55]. In this context, further studies should aim to study the implication of these aspects in diagnosis of persistent PCS [56].…”
Section: Mechanisms and Predisposing Factors For Persistent Post-conc...mentioning
confidence: 99%
“…Due to the multifactorial nature of sexuality, many factors such as neuroendocrine disruption, TBI-related cognitive changes, and other psychological and emotional factors alone or in combination could result in various presentations of post-TBI sexuality changes (Sander et al 2013;Latella et al 2018;Mahajan et al 2023). Findings by Fraser et al (2020) indicated depression as a mediator of associations between hyposexual changes, reduced social participation, and increased fatigue.…”
Section: Introductionmentioning
confidence: 99%